O Artigo De Opinião No Livro Didático De Língua Portuguesa: Desafios E Possibilidades Para A Produção Textual - Silva, Alciene Carvalho [UNIFESP] (2018)
This Thesis"S Main Objective Is Analyzing The Teaching-Learning Proposals For Text Production, Whose Focus Is The Discursive Genre Opinion Piece, Which Belongs To The Journalistic Sphere Of Discourse, But Which, When Re-Presented In Textbooks, Becomes Part Of The Pedagogical Discursive Universe. The Research Corpus Is Composed Of Two Collections Of Portuguese Language Textbooks For Ensino Fundamental Ii, Selected By The Pnld In 2014: Português Linguagens, By Authors William Roberto Cereja And Thereza Cochar Magalhães, And Vontade De Saber Português, By Authors Rosemeire Alves And Tatiane Brugnerotto. We Have Analyzed How The Activities Of Text Production, Based On The Journalistic Discursive Genre, More Specifically The Opinion Piece, Proposed In The Textbooks Of Portuguese Language For Ensino Fundamental Ii, Contribute To The Development Of Writing Skills Of Students In Elementary School. We Have Adopted In Our Research Both A Quantitative And Qualitative Approach. In Order To Do So, We Have Drawn On The The